The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/s11936-020-00846-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Temperature Management for Treatment of Cardiac Arrest

Abstract: This article is part of the Topical Collection on Arrhythmia Keywords Cardiac arrest I Therapeutic hypothermia I Targeted temperature management Abbreviations IHCA In-hospital cardiac arrest _ OHCA Out-of-hospital cardiac arrest _ PEA Pulseless electrical activity _ VT Ventricular tachycardia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
11
1
Order By: Relevance
“…The overall IHCA survival rates in both LBH (23.5%) and HBH (20.5%) were lower than recently reported across hospitals in the United States (26)(27)(28)(29). We also found a slight decline in the survival trend in both LBH and HBH during the study period in contrast with demonstrated improvement in IHCA survival outcomes over the last 2 decades (23,24,27). Lack of health insurance and underinsurance has been linked to higher in-hospital mortality in cardiac arrest patients (8,30,31).…”
Section: Discussioncontrasting
confidence: 72%
“…The overall IHCA survival rates in both LBH (23.5%) and HBH (20.5%) were lower than recently reported across hospitals in the United States (26)(27)(28)(29). We also found a slight decline in the survival trend in both LBH and HBH during the study period in contrast with demonstrated improvement in IHCA survival outcomes over the last 2 decades (23,24,27). Lack of health insurance and underinsurance has been linked to higher in-hospital mortality in cardiac arrest patients (8,30,31).…”
Section: Discussioncontrasting
confidence: 72%
“…2,3 Over the past decade, hospitals have devoted considerable effort toward improving IHCA survival by improving care delivery during the acute resuscitation phase [4][5][6] and the postresuscitation phase. 7 Despite these efforts, IHCA survival rates have plateaued in recent years, with mean survival of approximately 25%. 2,8,9 Given the high incidence and low survival for IHCA, efforts targeted toward prevention of IHCA could be impactful.…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital cardiac arrest (IHCA) affects nearly 290 000 hospitalized patients each year in the United States and is associated with poor survival and a high risk of neurological disability among survivors . Over the past decade, hospitals have devoted considerable effort toward improving IHCA survival by improving care delivery during the acute resuscitation phase and the postresuscitation phase . Despite these efforts, IHCA survival rates have plateaued in recent years, with mean survival of approximately 25% .…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of these two landmark trials were promising, there were several limitations that dampened the enthusiasm: they were open-label, their sample size the small with a high rate of screen failures (thus, raising concern for non-generalization), and at the time there were no established protocols for neuroprognostication post-CA and withdrawal of life-sustaining therapy (WLST) [ 36 ]. These limitations were subsequently addressed in the 2013 TTM1 trial, a RCT that analyzed 939 adult OHCA patients who remained unresponsive to verbal commands, and randomly assigned them to either temperature control at 33 °C or 36 °C for 24 h, followed by controlled active rewarming at 0.5 °C/h to 37 °C and subsequent normothermia until 72 h from randomization.…”
Section: Methodsmentioning
confidence: 99%